Prevalence of overweight and obesity among late adolescents in Jaffna district - Menaka, S.; Arasaratnam, V.; Surenthirakumaran, R. (Rajarata University of Sri Lanka, 2025)
Background: Adolescence is a period of life with specific health and developmental needs. The rising prevalence of overweight and obesity among adolescents poses a significant health risk which leads to early on set non-communicable diseases. Change in dietary habits and reduced physical activity contribute to the prevalence. Objective: This study aims to assess the overweight and obese status of 736 late adolescents (from 17-19 years) from Jaffna district based on Body Mass Index (BMI) and Waist to Hip Ratio (WHR) to support effective public health interventions. Methods: Multistage stratified random sampling with probability proportionate to size was used. During household visits, the first household was visited randomly and then every fourth house to the right was visited. In each selected household individuals aged 17-19 were listed and the elder one was selected with the date of birth. After obtaining the written consent, the socio demographic data was selected through an interviewer administrated questionnaire. Weight, height, waist circumference and hip circumference were measured as anthropometric measurements. Ethical clearance was obtained from Ethics Review Committee, Faculty of Medicine, University of Jaffna. Results: In the study 47.8% (n=352) of participants were males with the mean age of 18.06 (± 0.8) years and 52.2% (n=384) were females with the mean age of 18.07 (± 0.8). The overweight prevalence (BMI 25-29.9) was 9.1% (n=32) in males and 8.9% (n=34) in females, while obesity (BMI >30) affected 2.9% (n=10) males and 3.1% (n=12) females. The central obesity measured by WHR>0.9 was higher in females (17.2%, n=66) compared to males (8.5%, n=30). Conclusion: The study reveals a notable prevalence of overweight and obesity among adolescents in the Jaffna district. Central obesity is more prominent in females. These findings underscore the emerging risk of nutrition-related health problems in late adolescents and highlight the importance of implementing targeted public health interventions to promote healthy growth and prevent future complications.
Keywords: Adolescents; Jaffna; Obesity